Toll-like receptor activation during cutaneous allergen sensitization blocks development of asthma through IFN-gamma-dependent mechanisms - Haapakoski, R; Karisola, P; Fyhrquist, N; Savinko, T; Lehtimäki, S; Wolff, H; Lauerma, A; Alenius, H (2013)
Toll-like receptors (TLRs) are pattern-recognition receptors that have a pivotal role as primary sensors of microbial products and as initiators of innate and adaptive immune responses. We investigated the role of TLR2, TLR3, and TLR4 activation during cutaneous allergen sensitization in the modulation of allergic asthma. The results show that dermal exposure to TLR4 ligand lipopolysaccharide (LPS) or TLR2 ligand Pam 3 Cys suppresses asthmatic responses by reducing airway hyperreactivity, mucus production, Th2-type inflammation in the lungs, and IgE antibodies in serum in a dose-dependent manner. In contrast, TLR3 ligand Poly(I:C) did not protect the mice from asthmatic symptoms but reduced IgE and induced IgG2a in serum. LPS (especially) and Pam 3 Cys enhanced the activation of dermal dendritic cell (DCs) by increasing the expression of CD80 and CD86 but decreased DC numbers in draining lymph nodes at early time points. Later, these changes in DCs led to an increased number of CD8 + T cells and enhanced the production of IFN-γ in bronchoalveolar lavage fluid. In conclusion, dermal exposure to LPS during sensitization modulates the asthmatic response by skewing the Th1/Th2 balance toward Th1 by stimulating the production of IFN-γ. These findings support the hygiene hypothesis and pinpoint the importance of dermal microbiome in the development of allergy and asthma. © 2013 The Society for Investigative Dermatology.